2007
DOI: 10.1007/s00415-006-0491-6
|View full text |Cite
|
Sign up to set email alerts
|

CBF changes in drug naive juvenile myoclonic epilepsy patients

Abstract: Our results suggest that abnormal neural networks in the thalamus, hippocampus, brainstem and cerebellum are associated with JME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…This finding is consistent with the negative correlation found between right frontal lobe volume and JME disease duration in our previous study [25]. In an interictal SPECT study on drug naïve JME patients, we also reported a negative correlation between regional cerebral blood flow (rCBF) and the disease duration in frontal cortices [26]. These findings suggest that frontal lobe dysfunction in JME may change over time.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This finding is consistent with the negative correlation found between right frontal lobe volume and JME disease duration in our previous study [25]. In an interictal SPECT study on drug naïve JME patients, we also reported a negative correlation between regional cerebral blood flow (rCBF) and the disease duration in frontal cortices [26]. These findings suggest that frontal lobe dysfunction in JME may change over time.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, a serotonin 1A receptor PET study reported the reductions of serotonin 1A receptor binding potential in the raphe nucleus of pons, hippocampus, and anterior dorsolateral frontal cortex of JME patients suggesting an affected serotonin system [19]. Moreover, an interictal SPECT analysis of drug naïve JME patients revealed decreased rCBF in areas of the left hippocampus, subcallosal gyrus, thalamus, pons, and also showed negative correlations between rCBF and disease duration in the bilateral frontal cortices, caudate nuclei, left putamen, right anterobasal temporal lobe, bilateral brainstem [26]. The caudal raphe nuclei project to the cerebellar cortex and spinal cord, whereas rostal raphe nuclei project to the thalamus, nucleus accumbens, hypothalamus, amygdala, hippocampus, and the cortex [13].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This is in accordance with the few previous reports point to the role of the cerebellum in the development of JME. Tae et al (2007) assessed the regional cerebral blood flow abnormality in JME patients. They showed a significant regional cerebral blood reduction in bilateral thalami, red nucleus, midbrain, pons, left hippocampus, and in the cerebella, and an increase in the left superior frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%